Hemodynamic Characteristics of Patients With Suspected Coronary Heart Disease at Their Initial Visit - Cao, Haoyao; Li, Yiming; Zhao, Yiming; Xiong, Tianyuan; Liu, Zhan; Zheng, Tinghui; Chen, Mao (Frontiers in Physiology, 2021)
Purpose: It is difficult for doctors to decide whether patients with suspected coronary heart disease classified as Coronary Artery Disease Reporting and Data System (CAD-RADS) < 3 should be administered preventive treatment, or whether non-atherosclerotic chest pain should be considered. The aim of the current study was to investigate coronary hemodynamic characteristics in such patients, which may provide more information on their stenosis and be helpful for initial diagnoses. Methods: Two patient-specific models were reconstructed based on the coronary computed tomographic angiography underwent in 2012. Patient 1 was classiﬁed as CAD-RADS 0, and was readmitted to hospital due to coronary artery disease within 5 years. Patient 2 was classiﬁed as CAD-RADS 2, and has experienced no adverse events to date. Computational fluid dynamics analysis was used to obtain hemodynamic parameters including flow rate waveform, flow streamlines, time-average wall shear stress (TAWSS), and oscillatory shear index. Results: Patient 1 exhibited no physiological characteristics of right coronary artery flow waveform, large areas of low TAWSS, and slow blood flow in the proximal and middle segments of the left anterior descending branch. Patient 2 exhibited reduced coronary supply, small and separate areas of abnormal TAWSS, and a higher left anterior descending branch oscillatory shear index than patient 1. Conclusions: Hemodynamic abnormalities may play an important role in the prognosis of patients with coronary stenosis, and patient-specific hemodynamic characteristics may facilitate more accurate initial diagnosis, and better management. Overall hemodynamics (along the whole vessel) warranted attention at the time of the initial visit in patients classified as CAD-RADS < 3.